ANALISIS MISKONSEPSI MAHASISWA PADA MATERI PROGRAM LINEAR DILIHAT DARI ASPEK KOGNITIF - yanuarti, maghfiroh; Asmarawati, Endah (Pamulang university, 2024)
The aims of this research are 1) to describe the types of misconceptions and the factors that cause them in Management Study Program students at Pamulang University with a field independent cognitive style in rectangular plane material, 2) to describe the types of misconceptions and the factors that cause them in students at the Management Study Program at Pamulang University in this style. field dependent cognitive material on rectangular flat shapes. This type of research is descriptive research with a qualitative approach. The sample in this research were students in class 01SMJP007 of the Pamulang University Management Study Program for the 2022/2023 academic year. The research subjects consisted of 2 students with a field independent cognitive style and 2 students with a field dependent cognitive style. Subjects were selected based on the results of misconception diagnostic tests and recommendations from economics and business mathematics lecturers. The instruments used in this research were misconception diagnostic tests and interviews to determine the causes of misconceptions. The results of the research show that students are field independent, namely 1) classificational misconceptions, 2) theoretical misconceptions. The causes of misconceptions are associative thinking, the language used, lack of learning experience and lack of emphasis on material by lecturers. Misconceptions experienced by field dependent students are 1) classificational misconceptions including: 2) theoretical misconceptions. The causes of misconceptions are preconceptions, associative thinking, everyday language used, student learning experiences, lack of emphasis on material and lack of communication between lecturers and students.Keywords: Misconceptions; cognitive style; linear programming